Nest architecture of Pachycondyla striata Fr. Smith, 1858 (Formicidae, Ponerinae) - da Silva-Melo, A. [UNESP]; Giannotti, Edilberto [UNESP] (Birkhauser Verlag Ag, 2010)
Nine nests of Pachycondyla striata Fr. Smith, 1858 were excavated between 2006 and 2007 at the UNESP university campus in Rio Claro, SP, southeastern Brazil. The P. striata population was larger in the two nests excavated in the months of August and November, 2006. The nests of this species are simple and poorly elaborated, with chambers and tunnels close to the ground surface. P. striata places the pupae in chambers isolated from the other individuals. The lack of chambers with the specific purpose of conditioning food and garbage underscores the simplicity of these nests.
Keywords: Pachycondyla striata nest; Architecture nest; Ant colonies; Underground nests; Horizontal tunnels